Adoption of digital technologies, business model innovation, and financial and sustainability performance in start-up firms - Erkko Autio; Chiraphol N. Chiyachantana; Cynthia Castillejos-Petalcorin; Kun Fu; Raymund Habaradas; Yothin Jinjarak; Anang Muftiadi; Donghyun Park; Pattarawan Prasarnphanich; Pham Minh Quyên; Willem Smit (Asian Development Bank (ADB), 2024)
This report investigates the impact of digitalization on firm-level performance using survey data from 681 digital entrepreneurs across six Association of Southeast Asian Nations (ASEAN) countries. Results show that the reliance of the business on select digital applications and the digitalization of different aspects of the firm's business models were found to be potent drivers of business model experimentation in entrepreneurial businesses. We also observed consistent mediation effects of digitalization variables on performance through their effect on business model experimentation, although the digitalization variables also exhibited strong direct effects on performance. This last observation signals that the adoption of digital technologies by entrepreneurial businesses has more wide-ranging beneficial impacts than their facilitating effect on business model experimentation. We consider the findings reported here to be of significant value for the design of entrepreneurial and digitalization policies in Asian developing economies and in emerging economies more widely. Our analysis points to important performance implications of digital technology adoption by entrepreneurial businesses.
Keywords: L26; O32; O33; 330; digitalization; business model innovation; entrepreneurial performance; ASEAN; sustainability performance